Public availability of information from WFME-recognized accreditation agencies - Kahlo Baniadam; Zakia Arfeen; Mohammed Ahmed Rashid; Ming-Jung Ho; Sean Tackett (BMC, 2021)
Abstract The World Federation for Medical Education (WFME) Recognition Programme was created to ensure the comparability of medical school accrediting agencies, so that the schools accredited by those agencies would have similar educational quality. WFME explicitly values transparency and has recognition criteria that relate to agencies making information publicly available. Our study examined 20 WFME-recognized agencies' transparency by reviewing agency websites for 27 information elements related to accreditation standards, procedures, and processes. We contacted agencies as needed for information that we could not find on their websites. We were only able to retrieve additional information from 3 of the 12 agencies that we attempted to contact. We found that while 12 agencies had over 90% of expected information elements available, 6 agencies had less than 50%. Our findings illustrate barriers for those who wish to better understand medical school accreditation in some regions and raise questions about how comparable WFME-recognized agencies are.